The need for ecological momentary assessment in researching emotional factors in language education - Li, Xiaodong (Frontiers in Psychology, 2023)
Language learning is an emotional and dynamic process, which is marked by fluctuations in language learners’ positive and negative emotional variables (e.g., boredom, enjoyment, anxiety). Presumably, evidence can be found for an ecological view of the patterns and variations involved in language learners’ emotions under the influence of the interactive individual and contextual elements of classroom learning. The present study contends that an ecological momentary assessment (EMA), which is compatible with the complex dynamic system theory (CDST) can help to explore the dynamics of language learners’ emotional variables as they develop out of the process of classroom language learning. EMA is capable of tracing the moment-by-moment changes in a certain emotional trait in language learners as they are learning a foreign or second language. This innovative approach to research compensates for the shortcomings of retrospective studies (the delay of recalls) and also single-shot research designs (for data collection). It is fit for the assessment of the emergent patterns of L2 emotional variables. The distinctive features and pedagogical implications will be further discussed here.